Conector de cisalhamento tipo pino com cabeça para viga mista aço-concreto com laje alveolar - Sales, Marcel Willian Reis (2014)
Composite beams of steel and concrete are studied for some time. The mechanism of transfer of longitudinal shear stresses on the interface between the beam and the slab usually occurs by means of shear connectors. In this case, the set of two materials behavior depends on the strength and rigidity of the connector on the interface, being well known for connectors with pin-type head associated with massive concrete slab. However, there is little information on shear connectors with pin-type head associated with hollowcore slab concrete. This study aims to determine, by means of direct shear tests, the resistance of connectors with pin-type head when associated with cellular slab and precast concrete presence of cover concrete. Hollow core slabs are analyzed with two different heights and concrete cover of 40 mm in thickness. Is also varied the strength of concrete fill and rate of shear reinforcement at the link. The results are compared with normative prescriptions and suggestions for other jobs. At the end, we propose the modification of an expression commonly used to evaluate the resistance of stud bolt and alveolar slab so as to adapt it to the situation of cellular concrete slab with hood.